Selective sensing of adenosine monophosphate (AMP) over adenosine diphosphate (ADP), adenosine triphosphate (ATP), and inorganic phosphates with zinc(ii)-dipicolylamine-containing gold nanoparticles. Issue 17 (12th April 2021) - Reinke, Lena; Koch, Marcus; Müller-Renno, Christine; Kubik, Stefan
Abstract : Mixed monolayer-protected gold nanoparticles with surface-bound zinc(ii ) dipicolylamine units allow the selective detection of adenosine monophosphate in an aqueous solution. Abstract : Mixed monolayer-protected gold nanoparticles containing surface-bound triethylene glycol and dipicolylamine groups aggregated in water/methanol, 1 : 2 (v/v) in the presence of nucleotides, if the solution also contained zinc(ii ) nitrate to convert the dipicolylamine units into the corresponding zinc complexes. Nanoparticle aggregation could be followed with the naked eye by the colour change of the solution from red to purple followed by nanoparticle precipitation. The sensitivity was highest for adenosine triphosphate (ATP), which could be detected at concentrations >10 μM, and decreased over adenosine diphosphate (ADP) to adenosine monophosphate (AMP), consistent with the typically higher affinity of zinc(ii )-dipicolylamine-derived receptors for higher charged nucleotides. Inorganic sodium diphosphate and triphosphate interfered in the assay by also inducing nanoparticle aggregation. However, while the nucleotide-induced aggregates persisted even at higher analyte concentrations, the nanoparticles that were precipitated with inorganic salts redissolved again when the salt concentration was increased. The thus resulting solutions retained their ability to respond to nucleotides, but they now preferentially responded to AMP. Accordingly, AMP could be sensed selectively at concentrations ≥50 μM in an aqueous environment, even in the presence of other nucleotides and inorganic anions. This work thus introduces a novel approach for the sensing of a nucleotide that is often the most difficult analyte to detect with other assays.